The Influence of Family-Expressed Emotion on the Risk of Relapse in Patients with Schizophrenia: Outcomes from a Community Medicine Intervention - Wira, Muhammad Bagus; Nia, Sarah; Syaharani, Ramidha; Syariman, Ezrin; Amadea, Karindra; Pearl, Anastasia; Talitha, Khansa; Maramis, Margarita Maria (Universitas Airlangga, 2025)
Schizophrenia is a syndrome characterized by fundamental deviations in thinking, perception, and affect. Expressed emotion (EE) is a crucial risk factor in influencing the occurrence of relapse. In Indonesia, there is still no community therapy activity related to the family EE against the risk of relapse of schizophrenia patients. This is the underlying need for community psychiatry activities against families of patients with schizophrenia and related parties. This cross-sectional study was conducted in Puri, Mojokerto, Indonesia. The method was divided into three stages: field introduction, community diagnosis, and community therapy. In 36 schizophrenia patients, it was found that the level of EE experienced by the patients was relatively low, and the risk of recurrence within one year was around 43.27%. Based on these findings, the families of schizophrenia patients in Puri District can express good positive emotions towards their patients, which is in line with the relatively low risk of relapse. The author did an EE assessment by sharing a questionnaire as a short-term evaluation of the occurrence of relapse. As a continuation of the program, long-term evaluation will be returned to the community health centre and carried out by the program holder. Community medicine benefits community health centers, communities, and students by increasing family and community awareness of schizophrenia and improving the quality of community health centers and public health. Students also learn how to educate families with schizophrenia.